Microvascular reactivity, assessed by near-infrared spectroscopy and a vascular occlusion test, is associated with patient outcomes following cardiac surgery: A prospective observational study. Issue 5 (May 2018) - Butler, Ethan; Mahendran, Sajeev; Nguyen, John; Aneman, Anders
Abstract : BACKGROUND: Microvascular dysfunction in patients admitted to the ICU following cardiac surgery may be related to perioperative complications and increased resource utilisation even in the presence of acceptable systemic haemodynamic variables. OBJECTIVES: To assess the relationship between microvascular impairment using peripheral near-infrared spectroscopy at ICU admission and 6 h postadmission and the duration of mechanical ventilatory support, length of stay in ICU and in hospital. DESIGN: Prospective, observational cohort study. SETTING: Single-centre, tertiary-level cardiac ICU. PATIENTS: Sixty-nine adult patients following elective cardiac surgery excluding patients with on-going extracorporeal support or in whom tissue haemoglobin oxygen saturation (StO2 ) measurements were not feasible. MAIN OUTCOME MEASURES: Thenar and forearm StO2 in response to a vascular occlusion test to calculate desaturation and reperfusion slopes. A logistic regression model was used to ascertain the associations between StO2, desaturation and reperfusion slopes as well as cardiac index, mean arterial pressure, arterial lactate concentrations and prolonged (≥75th percentile) duration of mechanical ventilation, ICU length of stay and hospital length of stay. RESULTS: A reduced reperfusion slope at ICU admission was associated independently with prolonged mechanical ventilation at thenar (OR 0.08; 95% CI [0.02 to 0.47], P = 0.003) and forearm [OR 0.2 (0.04 to 0.59), P = 0.006] sites. Similarly, a reduced Rres was associated with prolonged ICU LOS at both thenar [OR 0.3 (0.13 to 0.77), P = 0.007] and forearm [OR 0.2 (0.05 to 0.62), P = 0.007] sites at ICU0 h, as well as ICU6 h [OR 0.2 (0.05 to 0.66), P = 0.004 and OR 0.05 (0.008 to 0.34), P = 0.002]. An increased Rdes was associated with prolonged hospital LOS at the thenar eminence at ICU0 h [OR 1.9 (1.4 to 2.3), P = 0.004] and ICU6 h [OR 6.7 (2.0 to 23), P = 0.002] as well as the forearm at ICU0 h [OR 1.5 (1.3 to 1.9), P = 0.004] and ICU6 h [OR 1.6 (1.3 to 2.1), P = 0.004]. CONCLUSION: In the early postoperative period following cardiac surgery, changes in thenar and forearm tissue oxygenation variables are associated with patient resource utilisation outcomes.